DESARROLLO AGROFORESTAL COMUNITARIO SUSTENTABLE EN LA REGIÓN FRONTERIZA MÉXICO - ESTADOS UNIDOS DE AMÉRICA - Luján Álvarez, Concepción; L. Falk, Constance; Erickson, Christopher A.; Mexal, John G.; Luján Álvarez, Humberto (Revista Mexicana de Ciencias Forestales, 2020)
The environmental and natural resources deterioration in the arid and semiarid zones have motivated a great interest in arder to look for a transition toward the sustainable development. This ecological condition includes areas in the border region between Mexico and the United States. A common prevalent situation along the border region is the inadequate wastewater treatment and in sorne cases, the absences of these systems. In addition, the conventional wastewater treatment systems are very expensive in order to be installed and operated, not providing the important advantages for the ecological and socio-economic growth. The Ojinaga Agroforestry Project (PACO) is a.n alternative that could direct ’those necessities, since it seeks to integrate approaches of sustainable development. A main component of this study is the use and management of wastewater· and irrigation water for the commercial production of. wood for fiber. In this sense, an important element is the involvement of the border community of Ojinaga, Chihuahua, Mexico, in the decision making process through the Search Conference Methodology. The social community participates in planning, implementing and assessing th’e actions for its development, including ecological, social and economic aspects. The purpose is to reduce the environmental pollution and the pressure on the natural resources. At the same time, these measures help to use and manage wastewater and irrigation water aiming to improve their quality and the salted soil conditions and abandoned lands, and generate better economic opportunities and sources of employment for the people in this border region.